«ПОГРАНИЧНЫЙ ЯЗЫК» КАК ОСОБЫЙ ПЕРЕВОДЧЕСКИЙ ФЕНОМЕН (Philological Studies, 2019)
Translation space conception is applied to the hierarchy of quality assessment criteria among witch harmony represents the highest level.